2020
DOI: 10.32539/bji.v6i1.9087
|View full text |Cite
|
Sign up to set email alerts
|

IFN-gamma and IL-4 Secretion After Stimulation of EC610 Fusion Antigens (ESAT-6-CFP-10) in Patients With Active Pulmonary TB And Latent TB

Abstract: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (M.tb) and is still a major health problem in the world. Immunity against tuberculosis is very complex because it involves almost all components of the immune system. One of the cells that are responsible for cell-mediated immunity are lymphocytes, especially T helper lymphocytes are divided into Th1 (proinflammatory cytokines IFN-?) and Th2 (anti-inflammatory cytokine IL-4). EC610 fusion antigens (ESAT-6-CFP-10) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Wibowo et al, 23 Bastian et al, 24 and Marpaung et al 25 reported no difference in IFN-γ levels after stimulation with ESAT-6/CFP-10 fusion in patients with active pulmonary TB and latent TB. It differs from Setiawan and Nugraha, 26 Safutri et al, 27 and Prihantika et al, 10 where the levels of IFN-γ in PBMC cells with active TB were higher than in latent TB PBMC cells after being stimulated by ESAT6/CFP-10 fusion. The differentiation in results may be due to the different types and doses of antigens, the status of TB patients who are primarily malnourished, and the possibility of recurrent pulmonary TB disease.…”
Section: Dicky Santosa Et Al: Effect Of Esat-6 On Phagocytosis Activi...mentioning
confidence: 58%
See 1 more Smart Citation
“…Wibowo et al, 23 Bastian et al, 24 and Marpaung et al 25 reported no difference in IFN-γ levels after stimulation with ESAT-6/CFP-10 fusion in patients with active pulmonary TB and latent TB. It differs from Setiawan and Nugraha, 26 Safutri et al, 27 and Prihantika et al, 10 where the levels of IFN-γ in PBMC cells with active TB were higher than in latent TB PBMC cells after being stimulated by ESAT6/CFP-10 fusion. The differentiation in results may be due to the different types and doses of antigens, the status of TB patients who are primarily malnourished, and the possibility of recurrent pulmonary TB disease.…”
Section: Dicky Santosa Et Al: Effect Of Esat-6 On Phagocytosis Activi...mentioning
confidence: 58%
“…Macrophage cells also produce IL-10 through programmed cell death protein 1 (PD1) to reduce apoptosis and stimulate Tregs to secrete IL-10 due to decreased production of CD4+ cells. 29 Safutri et al 27 showed an increase in IL-4 In PBMC cells of active TB patients after being induced by ESAT-6/CFP-10. IL-4 is a cytokine mainly produced by Th2 cells, which is also predicted to shift from Th1 cells to Th2 cells.…”
Section: Dicky Santosa Et Al: Effect Of Esat-6 On Phagocytosis Activi...mentioning
confidence: 99%